(untitled) (Research, Society and Development, 2022)
The aim of the present study was to adapt the Altruistic Attitudes Scale to the Brazilian context. It was intended to know the validity based on the internal structure and the reliability through the compound reliability. For this purpose, 421 university students with an average age of 18.9 years old (SD = 0.79), mostly female (57.2%), collaborated. Participants answered demographic questions and a battery of six measures, including the Altruistic Attitudes Scale, which theoretically covers three factors: behavioral, cognitive and affective. From the factor analysis it was possible to identify three factors that allowed explaining 64.2% of the total variance, being interpreted as cognition (37.2%), affection (13.9%) and behavior (12.9%). The results are discussed in the light of investigations carried out, and thus, it is suggested that the factorial structure of the EAA has a three-factor model, therefore corroborating with the original study.